Health benefits of Kung Fu: A systematic review - Tsang, T. W. M.; Kohn, M.; Chow, C. M.; Singh, M. F. (Journal of Sports Sciences, 2008)
The Chinese martial arts (Kung Fu) have existed for centuries and are generally accepted as being beneficial for health without much empirical data. The aim of this systematic review was to assess the health effects of "hard" Kung Fu styles by performing electronic and manual searches of the literature. The aspects of health and the Kung Fu style examined varied between most studies; in some cases, the martial art group consisted of practitioners of other martial art styles also. Of 2103 references identified, only nine papers were eligible and reviewed. All were observational studies, observing a range of health aspects possibly related to Kung Fu training or performance. Our findings suggest that there is no evidence that Kung Fu practice is associated with the prevention or treatment of any health condition. However, as a moderate- to high-intensity form of aerobic exercise, it may confer benefits similar to those attributed to other aerobic training modalities. However, this hypothesis remains to be tested in clinical trials. Physiological benefits (e.g., aerobic capacity and bone density) may be associated with long-term Kung Fu practice. Future research in this area should adopt experimental designs, clearly identifying eligibility criteria, testing and training protocols, and include health-related outcomes and documentation of adverse events, to advance knowledge in this field.